Democracy and political change in Sub-Saharan Africa - Wiseman, John A. (London ; New York : Routledge, 1995)
The book provides readers a set of case studies covering a diverse range of African states in order to identify the major causes of change and the movement towards democracy.
t
Incluye referencias bibliograficas.